Właściwości litologiczne, chemiczne i fizyczne wybranych rodzajów czwartorzędowych osadów węglanowych = Lithological, chemical and physical properties of quaternary calcareous lacustrine sediments - Żurek-Pysz, Urszula (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Calcareous quaternary sediments have been tested. The following research methods were applied: microscopic observations in transparent light, X-ray analysis, infrared spectroscopy, scanning analysis and chemical analysis. Holocene carbonate sediments consist of major components: water and mineral, phytogenic and zoogenic substance.
Keywords: 2 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zagospodarowanie zlewni" (21-22.06.2001)